Click Stimulus Electrocochleography Versus MRI With Intratympanic Contrast in Ménière's Disease: A Systematic Review. Issue 5 (June 2016) - Ziylan, Fuat; Smeeing, Diederik P. J.; Stegeman, Inge; Thomeer, Hans G. X. M.
Abstract : Objective: To evaluate the diagnostic value of electrocochleography compared with magnetic resonance imaging (MRI) with intratympanic gadolinium administration to diagnose endolymphatic hydrops in patients with Ménière's disease. Data Sources: An electronic search was performed in the PubMed, EMBASE, and Cochrane databases on September 15, 2015. A systematic search was conducted. Articles were included if written in English, Dutch, German, or French language. Study Selection: Original studies reporting on the diagnostic value of electrocochleography compared with MRI with intratympanic gadolinium administration, were included. Data Extraction: The methodological quality of the studies was independently assessed by two reviewers using an adjusted version of the Quality Assessment of Diagnostic Accuracy Studies (QUADAS) tool. The results of the diagnostic values of both tests were extracted. Data Synthesis: We performed analyses for the sensitivity, specificity, positive predictive value, and negative predictive value of compared electrocochleography with MRI with intratympanic gadolinium administration in patients with definite Ménière's disease. Conclusion: The results of this systematic review, based on a very low number of patients, show there is a relative low sensitivity and negative predictive value for click stimulus electrocochleography compared with MRI with intratympanic gadolinium administration for detecting endolymphatic hydrops in patients with definite Ménière's disease. Abstract : Supplemental Digital Content is available in the text